A Simulation Study of Depot with Multiple Temperature Modes: Maximum Flow Estimation - Nedvědová, Marie; Pozdílková, Alena; Marek, Jaroslav; Bažant, Michael (IEEE (Institute of Electrical and Electronics Engineers), 2019)
The aim of this paper is to make a truck loading simulation in a large area with several warehouses each with a given temperature mode of stored goods (frozen, refrigerated, and unrefrigerated goods). When loading goods in different temperature modes, time delays occur when trucks are crossing between ramps (ramps for various temperature modes are separated). The problem is that if the number of ramps is insufficient, queues may arise. The aim of the paper is to quantify the dependence of the loading time on the number of loaded pallets where we consider usually achievable loading area limits of trucks when planning multiple trips. We assume that customer order quantities are given by a Beta distribution. Knowledge of this density estimate allow us to assess the maximum flow through the depot. Arena software is used for the simulation.
Simulační studie úložiště s více teplotními režimy: maximální odhad průtoku
Keywords: depot; flow of goods; minimizing queues; loading simulation; depo; tok zboží; minimalizace fronty; simulace nakládky